(untitled) - Boschman, LaMar; (1953-...) (U.S.A., 1995)
The Rebirth of Music is quickly becoming a classic in its presentation of the Bible's major emphasis on music. You will discover why music is mentioned 989 times in the Scriptures and why God places such a major priority on it. Some of the topics include
Keywords: Church music